Almacenamiento masivo de sentencias nmea del módulo gps en memorias mmc/sd para su posteríor utilización en mapas de posicionamiento - Gutiérrez Cevallos, Ricardo (2011)
The following project consists on the design and implementation of a system capable of performing mass storage of NMEA sentences from a GPS LEA-5S receiver module. The prototype is used as functional tools a GPS receiver, an ET-MINI SD/MMC board, a microcontroller and a MMC/SD card. The main purpose is to store large amounts of data corresponding to NMEA strings in MMC or SD cards, and then use the stored information in the determination of position and trajectory maps. The GPS receiver module determines a location using satellite information, which is simultaneously delivered to the PIC, which selects the GPGGA strings, which belongs to the NMEA protocol, and then records these strings in a file on the MMC/SD card. The microcontroller used is a PIC 18F4520, programmed in MIKRO BASIC PRO to control the communication with a SMARTGPS board and for recording sentences in memory using the ET-MINI SD/MMC board.